2014
DOI: 10.1103/physrevb.89.115301
|View full text |Cite
|
Sign up to set email alerts
|

Phonon scattering in strained transition layers for GaN heteroepitaxy

Abstract: Strained transition layers, which are common for heteroepitaxial growth of functional semiconductors on foreign substrates, include high defect densities that impair heat conduction. Here, we measure the thermal resistances of AlN transition layers for GaN on Si and SiC substrates in the temperature range 300 < T < 550 K using time-domain thermoreflectance. We propose a model for the effective resistance of such transition films, which accounts for the coupled effects of phonon scattering on defects and the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 57 publications
6
103
1
Order By: Relevance
“…The mass density ( = 6087 kg/m 3 [34], = 3220 kg/m 3 [35]) and specific heat values with their temperature dependencies were also taken from the literature [36]- [37]. The thermal boundary resistance (TBR) at the GaNSiC interface associated with the AlN nucleation layer was set to a constant value of 5 m 2 -K/GW, in agreement with recently reported values measured by time-domain thermal reflectance (TDTR) [30]- [31]. The thermal properties of the indium solder were taken as the default values in COMSOL Multiphysics.…”
Section: Numerical Modelingmentioning
confidence: 94%
See 1 more Smart Citation
“…The mass density ( = 6087 kg/m 3 [34], = 3220 kg/m 3 [35]) and specific heat values with their temperature dependencies were also taken from the literature [36]- [37]. The thermal boundary resistance (TBR) at the GaNSiC interface associated with the AlN nucleation layer was set to a constant value of 5 m 2 -K/GW, in agreement with recently reported values measured by time-domain thermal reflectance (TDTR) [30]- [31]. The thermal properties of the indium solder were taken as the default values in COMSOL Multiphysics.…”
Section: Numerical Modelingmentioning
confidence: 94%
“…The values of 300 = 170 W/m-K and = 1.44 for GaN [30]- [31] and 300, = 490 W/m-K, 300, = 390 W/m-K, and = 1.49 for 4H-SiC [32]- [33] were taken from the literature. The mass density ( = 6087 kg/m 3 [34], = 3220 kg/m 3 [35]) and specific heat values with their temperature dependencies were also taken from the literature [36]- [37].…”
Section: Numerical Modelingmentioning
confidence: 99%
“…The TBReff can be a significant thermal barrier for heat transfer from the GaN HEMT to the diamond substrate; moreover, its temperature dependence is an important factor for consideration in device design and reliability assessment. It has been previously reported that the TBReff of GaN/AlN/SiC increases substantially with temperature [5], whereas another study suggested only a moderate increase in TBReff for both GaN/AlN/SiC and GaN/AlN/Si from 300 K to 550 K [6]. In both of these, the TBReff is effectively dominated by the AlN nucleation layer, which has a decreasing thermal conductivity with temperature due to phonon-phonon scattering and lattice imperfection scattering.…”
Section: Introduction Lgan/gan High Electron Mobility Transistors mentioning
confidence: 90%
“…The sensitivity shows different magnitudes on different timescales following the spatial and temporal evolution of heat, which diffuses from the gold surface to the GaN layer, and deep into the diamond substrate. The measurement is not sensitive to the thermal conductivity of the Au transducer (Au) or the GaN layer (GaN) on any distinctive timescale, and hence reported values including their temperature dependencies were assumed for Au [9] and GaN [6]. The thin AlGaN barrier layer (~20 nm) was included in the lumped thermal resistance between Au and GaN, TBRAu-GaN.…”
Section: Samples and Measurementmentioning
confidence: 99%
“…While applications such as GaN transistors [2,3] and light emitting diodes (LEDs) [4] require high thermal conductivity substrates to dissipate heat, the performance of thermoelectric and thermal insulation devices can be significantly enhanced by reducing their thermal conductivity [5,6]. In many of these applications, phonon boundary scattering is the dominant resistance to heat flow, making the detailed understanding of this process essential for advancing applications.…”
Section: Introductionmentioning
confidence: 99%